Construction and analysis of protein-protein interaction network to identify the molecular mechanism in laryngeal cancer - Sarahani Harun; Nurulisa Zulkifle (Penerbit Universiti Kebangsaan Malaysia, 2018)
Laryngeal cancer is the most common head and neck cancer in the world and its incidence is on the rise. However, the molecular mechanism underlying laryngeal cancer pathogenesis is poorly understood. The goal of this study was to develop a protein-protein interaction (PPI) network for laryngeal cancer to predict the biological pathways that underlie the molecular complexes in the network. Genes involved in laryngeal cancer were extracted from the OMIM database and their interaction partners were identified via text and data mining using Agilent Literature Search, STRING and GeneMANIA. PPI network was then integrated and visualised using Cytoscape ver3.6.0. Molecular complexes in the network were predicted by MCODE plugin and functional enrichment analyses of the molecular complexes were performed using BiNGO. 28 laryngeal cancer-related genes were present in the OMIM database. The PPI network associated with laryngeal cancer contained 161 nodes, 661 edges and five molecular complexes. Some of the complexes were related to the biological behaviour of cancer, providing the foundation for further understanding of the mechanism of laryngeal cancer development and progression.